Disiplin Kerja Mempengaruhi Kinerja Karyawan Pt Fast Food Indonesia Tbk Kentucky Fried Chicken (KFC) Di Kota Pekanbaru - Asnahwati, Asnahwati (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research is motivated by less optimal employee performance and low employee discipline. This research was conducted at PT. Fast Food Indonesia Tbk Kentucky Fried Chicken (KFC) Arifin Ahmad, Pekanbaru city. This study aims to determine the effect of work discipline on employee performance. This research involved all employees of PT. Fast Food Indonesia Tbk Kentucky Fried Chicken (KFC) Arifin Ahmad Pekanbaru city as many as 35 people as a population and all of them were used as samples because the total population did not reach 100 people. The sampling technique used was a census technique. While the analytical method used is descriptive and quantitative analysis. Data processing using SPSS version 23. Based on the results of research with an analysis of the influence of work discipline on employee performance at PT. Fast Food Indonesia Tbk Kentucky Fried Chicken (KFC) Arifin Ahmad Pekanbaru city, it can be concluded that: work discipline has a positive and significant effect on employee performance. This is evidenced by the simple regression equation Y = 11.425 + 0.777X +e and the results of the t test obtained tcount greater than ttable (13.784 > 2.03452) with a significance level of 0.000 less than 0.05 (0.000 <0.05) . From the determination test it is known that (R2) is 0.852 which means that the work discipline variable has an influence of 85.2% on employee performance at PT. Fast Food Indonesia Tbk Kentucky Fried Chicken (KFC) Arifin Ahmad Pekanbaru city, the remaining 14.8% is influenced by other variables not examined in this study.